2020
DOI: 10.15294/jpii.v9i4.23166
|View full text |Cite
|
Sign up to set email alerts
|

Local Wisdom and Laboratory Experiment-Based Extension Booklet Development for Wadi Makers of Elementary-Educated and Dropout Society in Central Kalimantan

Abstract: Wadi is one of traditionally fermented food types using basic materials of fish, salt, and lumu. As nutritive traditional food, wadi quality needs to be developed and maintained through social education. Wadi production innovation has not been done yet by the wadi makers since their information is limited on production techniques for better quality wadi. To promote local wisdom conservation, non-formal education for low educated-wadi makers is needed using simple media. Laboratory experiment and local wisdom-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Thus, education can be said to be a process of developing cultural values and civilization in society (Septiarti et al, 2017). Local culture including the local wisdom of an area can be preserved through formal education in schools and non-formal in the community (Dewi et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, education can be said to be a process of developing cultural values and civilization in society (Septiarti et al, 2017). Local culture including the local wisdom of an area can be preserved through formal education in schools and non-formal in the community (Dewi et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…These competencies can be realized through a learning process that is centered on students and an effective learning process (Dewi et al, 2020). Effective learning requires innovation in the field of education, such as learning that combines science and ethnoscience (Dwianto et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, several studies have concluded that booklets can be used as a medium for food safety literacy because they can increase food safety knowledge which remains high (within one to three months after the intervention is carried out), effective for transmitting food safety information for adults, and suitable for use in societies with heterogeneous educational profiles because it is simple, easy to understand and systematic. [5][6][7] Furthermore, booklets are widely used as media for health promotion because they have advantages such as low production costs, complete and easyto-understand information, attractive designs that make a person more interested and less bored to read them frequently, and portability. 8 As stated by WHO through the Health Promotion Glossary, health behavior is basically shaped by the social, cultural, residential, and occupational environment.…”
Section: Introductionmentioning
confidence: 99%